2011
DOI: 10.1007/s11999-010-1441-2
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Reduces Allogenic Transfusion in Revision Hip Arthroplasty

Abstract: Background Revision THA is associated with high blood loss and a high probability of blood transfusion in the perioperative period. In November 2003, government legislation established the Blood Utilization Program at our center to reduce the rate and risks associated with allogenic transfusion. Questions/purposes The purposes of this study were to (1) determine whether the allogenic transfusion rate in patients undergoing revision THA decreased in those who were reviewed preoperatively by the Blood Utilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 24 publications
(23 reference statements)
0
20
0
1
Order By: Relevance
“…The TXA doses used in this study were the following: no‐IVTA group, 2 g topical; IVTA‐I and IVTA‐II groups, 2 g topical and 1 g IV; and TITA group, 3 g topical and 1 g IV (Tables and ). The TXA dose (4 g) used in the TITA group was higher than that in other studies (systemic dose range, 1‐3 g) . However, only 3 of the 4 g of TXA in the TITA group in this study was used topically.…”
Section: Discussionmentioning
confidence: 58%
“…The TXA doses used in this study were the following: no‐IVTA group, 2 g topical; IVTA‐I and IVTA‐II groups, 2 g topical and 1 g IV; and TITA group, 3 g topical and 1 g IV (Tables and ). The TXA dose (4 g) used in the TITA group was higher than that in other studies (systemic dose range, 1‐3 g) . However, only 3 of the 4 g of TXA in the TITA group in this study was used topically.…”
Section: Discussionmentioning
confidence: 58%
“…14 Multiple prospective studies showed that tranexamic acid is effective in reducing blood loss and transfusion requirements in orthopedic patients undergoing hip and knee arthroplasty without an increased risk of thromboembolic disease. 1,8,[15][16][17] Furthermore, the medication is inexpensive and easy to administer around the time of surgery. 18 Although there has been no reported increased risk of cardiovascular complications after intravenous tranexamic acid administration, its use in high-risk patients undergoing total hip arthroplasty and total knee arthroplasty is controversial.…”
mentioning
confidence: 99%
“…Chances are that CKD patients have poor surgical results [17] with the combination of their own medical problems [18,19], including infections, blood transfusions, medical complications, re-admissions and death rate, and their own diseases which have been reported as an independent risk factor. Generally, with lower levels of hemoglobin and a higher risk of blood loss, CKD patients take a higher risk of transfusions [20].…”
Section: Discussionmentioning
confidence: 99%